Software Development to Reduce Misconceptions Using Conceptual Change Text Strategy on Chemical Bonding Matter - Sovranita Ramadhani Setiawan Putri; Sukarmin Sukarmin (International Journal of Chemistry Education Research, 2020)
The aims of this research is to determine the feasibility of software to reduce misconception on students using conceptual change text strategy on chemical bonding matter. This research is using Research & Development (R&D) design with X IPA MAN Sidoarjo’s students as a subject. Instrument used are student responses, student activity observation, and pretest-posttest sheet. Software developed using PHP (Hypertext Preprocessor) programming language. The result analyzed by a descriptive quantitative method that can be conclude as (1) The validity of software is valid showed by content validity average percentage is 88,57% with very valid  criteria and construct validity average percentage is 88,89% with very valid  criteria (2) the practicity of software got 87,41% with very practice criteria (3) Software effective in detect and reduce misconception that showed by percentage the average shift of conception from misconception to know concept is 83.53%.Keywords: software, misconception, conceptual change text, chemical bonding.